Displacement response of submerged floating tunnel with flexible boundary under explosion load. Issue 2 (January 2021) - Gang, Luo; Shaokang, Pan; Yulong, Zhang; Yi, Ren; Kai, Xiong
In this study, a single-span submerged floating tunnel (SFT) is simplified as an elastic supporting beam model with movable ends. This model is used to analyze the displacement response of the SFT subjected to an underwater explosion in an ocean environment. The effects of the shock wave pressure and bubble pressure are considered simultaneously. The dynamic equilibrium equation was established based on D'Alembert's principle. When the pipe segment of the SFT vibrates, the additional inertia force and the damping force of the surrounding water to the pipe are calculated using the Morison equation. The motion differential equation of an SFT under the load of an underwater explosion is obtained using the Galerkin method. The displacement analytical expressions of an SFT under four different stages of load are derived, and a comprehensive analysis is performed to assess the influence of key parameters, including the brace stiffness, damping, scaled distance, and bubble oscillation frequency, on the displacement of the SFT. It was observed that the key parameters mentioned above all significantly influence the displacement response of the SFT. Some reasonable suggestions for different parameters are proposed to provide a reference for the SFT design.